Colistin and doripenem combinations against Pseudomonas aeruginosa: profiling the time course of synergistic killing and prevention of resistance. (23rd February 2015) - Ly, Neang S.; Bulitta, Jürgen B.; Rao, Gauri G.; Landersdorfer, Cornelia B.; Holden, Patricia N.; Forrest, Alan; Bergen, Phillip J.; Nation, Roger L.; Li, Jian; Tsuji, Brian T.
Abstract: Objectives: Colistin is an 'old' drug, which is being increasingly utilized due to limited therapeutic options. However, resistance emergence during monotherapy is concerning. Here, our objective was to optimize colistin combinations against Pseudomonas aeruginosa by profiling the time course of synergistic killing and prevention of resistance. Methods: Hollow-fibre infection models over 10 days simulated clinically relevant dosage regimens of colistin and doripenem against two heteroresistant P. aeruginosa strains (MIC 1 mg/L) and one resistant (MIC 128 mg/L) strain (inoculum 10 9.3 cfu/mL). New mathematical mechanism-based models (MBMs) were developed using S-ADAPT. Results: Against heteroresistant P. aeruginosa strains, colistin monotherapy resulted in initial killing (up to 2.64 log10 cfu/mL) within 24 h followed by regrowth. High-intensity combinations involving free steady-state colistin concentrations of 5 mg/L achieved complete eradication (>9.3 log10 killing) within 48 h. These combinations achieved synergy with up to 9.38 log10 greater killing compared with the most active monotherapy. Against the colistin-resistant strain, the combination yielded marked initial synergy with up to 6.11 log10 cfu/mL bacterial reductions within 72 h followed by regrowth. The MBMs quantified total and resistant subpopulations and the proposed synergy between colistin and doripenem. Conclusions: Our findings provide insight into optimal antibiotic treatment and may serve as a framework for new drug combinations and combination modelling.